Total English Upper-Intermediate. Students Book - Acklam, Richard and Araminta Crace (Harlow Pearson Education Limited, 2006)
Total English is a new course for young adults and adults. It provides solutions to the challenges teachers and students face every day with a complete package of effective, easy-to-uae resources.
Keywords: English Practice